Customized Design 3D Printed PLGA/Calcium Sulfate Scaffold Enhances Mechanical and Biological Properties for Bone Regeneration - Liu, Tao; Li, Zhan; Zhao, Li; Chen, Zehua; Lin, Zefeng; Li, Binglin; Feng, Zhibin; Jin, Panshi; Zhang, Jinwei; Wu, Zugui; Wu, Huai; Xu, Xuemeng; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Polylactic glycolic acid copolymer (PLGA) had been widely used in tissue engineering due to its good biocompatibility and degradation properties. However, the mismatched mechanical and unsatisfactory biological properties of PLGA limit further application in bone tissue engineering. Calcium sulfate (CaSO4) is one of the most promising bone repair materials due to its non-immunogenicity, well biocompatibility, and excellent bone conductivity. In this study, aiming at the shortcomings of activity-lack and low mechanical of PLGA in the treatment of bone defect, customized-designed 3D porous PLGA/CaSO4 scaffolds were prepared by 3D printing. We first studied the physical properties of PLGA/CaSO4 scaffolds and the results showed that CaSO4 improved the mechanical properties of PLGA scaffolds. In vitro experiments showed that PLGA/CaSO4 scaffold exhibited good biocompatibility. Moreover, the addition of CaSO4 could significantly improve the migration and osteogenic differentiation of MC3T3-E1 cells in the PLGA/CaSO4 scaffolds, and the PLGA/CaSO4 scaffolds made with 20 wt% CaSO4 exhibited the best osteogenesis properties. Therefore, calcium sulfate was added to PLGA could lead to customized 3D printed scaffolds for enhanced mechanical properties and biological properties. The customized 3D-printed PLGA/CaSO4 scaffold shows huge potential for precisely repairing irregular load-bearing bone defects.